Evaluation of WISP1 as a candidate gene for bone mineral density in the Old Order Amish - Xing Wang (Nature Portfolio, 2018)
Abstract Wnt1-inducible signaling pathway protein-1 (WISP1) is a novel target of the Wnt pathway for modulating osteogenesis and improving bone strength. However, it is not clear if genetic variants in the WISP1 region are associated with bone mineral density (BMD) in human. The aim of this study is to investigate the role of genetic variation in WISP1 gene as a determinant of BMD in 1,510 Old Order Amish (OOA). We performed regional association analysis of 58 tag variants within 5 kb upstream and downstream to WISP1 with BMD and found 5 variants that were associated with BMD at multiple skeletal sites (P values from 2.89 × 10−6 to 1.62 × 10−2), with some significant associations even after adjustment for multiple comparisons. To replicate these results in an independent dataset, we performed a look-up of BMD associations with these variants in European ancestry subjects from the large GEFOS Consortium and observed the nominal associations of two of these variants with BMD (P values: 0.031 to 0.048). In conclusion, we have demonstrated that genetic variants surrounding WISP1 are associated with BMD at multiple skeletal sites in the OOA, thus influencing osteoporosis risk. These results support a role for the WISP1 gene on influencing variation in BMD.